Penegakan Hukum Terhadap Anak Sebagai Anggota Geng Motor Pelaku Kekerasan Yang Mengakibatkan Kematian Dikaitkan Dengan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak: Penegakan Hukum Terhadap Anak Sebagai Anggota Geng Motor Pelaku Kekerasan Yang Mengakibatkan Kematian Dikaitkan Dengan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak - Shinta Intan Sari; Eni Dasuki Suhardini; Dani Durahman; Yeti Kurniati (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
Criminal activity by motorcycle gangs has increasingly emerged as a social problem in Indonesia, especially in urban areas. This phenomenon shows the dynamic nature of crime, with robbery and murder being the most common offenses. Alarmingly, most perpetrators are minors. Cases involving children require special legal treatment to ensure the fulfillment of their rights and protection. The formal justice system, although well-structured, often fails to provide a positive impact for children, as it can cause trauma, stigmatization, and potential violence or exploitation. This study uses an empirical legal approach, which relies on factual data obtained from observations and interviews. The findings indicate that, first, violent crimes committed by minors resulting in death are punishable by more than seven years under the Criminal Code and Child Protection Law, but sentencing follows the juvenile justice system emphasizing diversion and restorative justice. If diversion is not possible, judges impose penalties based on the SPPA Law, with a maximum of half the adult sentence. However, the diversion process often faces implementation barriers. Second, although law enforcement efforts against motorcycle gang crimes have been intensified, their effectiveness remains limited due to various structural and social constraints that hinder optimal enforcement.